An IFOC-DSVPWM Based DC-Link Voltage Compensation of Z-Source Inverter Fed Induction Motor Drive for EVs. (25th June 2015) - Akkarapaka, Ananda Kumar; Singh, Dheerendra
Abstract : The drop in DC-link voltage of adjustable speed drives (ASD) occurs mainly due to the increase in output power demands. This may lead to inefficient operation and eventually the tripping of the drive. This paper presents a Double Space Vector Pulse Width Modulation (DSVPWM) technique for boosting and compensating the DC-link voltage of Z-source inverter (ZSI). The DSVPWM technique estimates the required shoot through period of the Z-source inverter to maintain the DC-link voltage constant at the desired level through capacitor voltage control. The DSVPWM can obtain maximum boost at any given modulation index in comparison to simple boost control (SBC) method. It also utilizes the dead time more effectively. The speed control of the ZSI fed induction motor drive is done by employing indirect field-oriented (IFO) control method. A 32-bit DSP (TMS320F28335) is used to implement the IFOC-DSVPWM method for ZSI. The power structure and the modulation technique are well suited for electric vehicle application.